Factor x^2 out of the first two terms to get x^2(x - 4) + 3x - 12 = 0. Factor a 3 out of the last two terms to get x^2(x - 4) + 3(x - 4) = 0. Rewrite the equation to get (x^2 + 3)(x^2 - 4) = 0. Therefore, one of the solutions to the equation is x - 4 = 0. Solve for x to get x = 4. The other solutions come from x^2 + 3 = 0, or x^2 = -3. This results in imaginary solutions, so the only real solution is 4.
Final answer: x = 4 is the only real solution.
Write something about yourself. No need to be fancy, just an overview.